2013
DOI: 10.1093/ckj/sfs175
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis by the book? Treatment of renal failure in a 101-year-old patient

Abstract: While dialysis historically began as treatment intended for younger patients, it has, over time, increasingly been extended to treat elderly patients with a high comorbidity burden. Data on the outcomes of dialysis in these patients show that in some cases it confers no benefit and may be associated with functional decline. We describe a 101-year-old male patient with chronic kidney disease (CKD), admitted to the intensive care unit (ICU) with exacerbation of heart failure and sepsis. He experienced acute dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Historically renal replacement therapy (RRT) was only considered a feasible treatment option in younger patients with little comorbidity [1,2]. In 1984 a survey revealed that half of nephrologists would not offer dialysis to a 50-year-old with ischaemic heart disease [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically renal replacement therapy (RRT) was only considered a feasible treatment option in younger patients with little comorbidity [1,2]. In 1984 a survey revealed that half of nephrologists would not offer dialysis to a 50-year-old with ischaemic heart disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Two decades later, Oreopoulous et al warned that 21st century nephrologists will be mainly practicing geriatric medicine and nephrologists needed to prepare for this "coming of age" [4]. True to that statement, today HD is considered a viable treatment option for all ages including the very elderly as a result of positive advances in medicine [2].…”
Section: Introductionmentioning
confidence: 99%